One-dimensional hopping transport in energetically disordered systems in presence of a strong biased field - Fateev, M.P. (Вопросы атомной науки и техники, 2012)
This report is devoted to the study of hopping drift mobility of charge carries in one-dimensional regular chain of localization site with energetic disorder. The individual jump rate was assumed to follow Miller-Abrahams type transition with nearest neighbor hopping. Exact results were obtained for the temperature and field dependence of the diffusion constant D(T,E) and drift velocity V(T,E) in a system with uncorrelated energetic disorder. Исследуется прыжковый дрейф носителей заряда в одномерной регулярной решетке с энергетическим беспорядком. Предполагается, что прыжки происходят между ближайшими узлами по закону Миллера-Абрахамса. Получены точные аналитические выражения для температурной и полевой зависимости коэффициента диффузии и скорости дрейфа для системы с не коррелированным беспорядком энергий. Досліджується стрибковий дрейф носіїв заряду в одномірній регулярній гратці з енергетичним безладдям. Передбачається, що стрибки відбуваються між найближчими вузлами за законом Міллера-Абрахамса. Отримані точні аналітичні вирази для температурної й польової залежності коефіцієнта дифузії й швидкості дрейфу для системи з не корельованим безладдям енергій.